Experiential Attunements in an Illuminated City at Night: A Pedagogical Writing Experiment. Issue 2 (3rd July 2019) - Zhang, Vickie; Kelly, David; Rodriguez Castro, Laura; Iaquinto, Benjamin Lucca; Hughes, Ainsley; Edensor, Tim; McKay, Campbell; Lobo, Michele; Kennedy, Melissa; Wolifson, Peta; Ratnam, Charishma; Buckle, Caitlin; et al.
Abstract : This article traces stories of singular footsteps taken on a collective meandering through Brisbane city, as a pedagogical experiment in writing for geographers. The diverse encounters recounted here took place as part of an extended workshop on the topic of light, beginning with an afternoon discussion, and ending in an evening walk through the illuminated city. This paper aims to do two things through the example of light: firstly, it explores the experiential attunements enacted in the event by resonating practices of talk with practices of movement, speculating on the enablements afforded by the conditions of the workshop. Secondly, presenting a range of writing that emerged out of this passage from world to word, this article is a performance of the diverse translations necessary to writing attunement. Refracted through an extended introduction by the event organisers, the vignettes that emerged from the day are then presented as something of a virtual walk in themselves: speaking to the entangled histories of the event, our bodies, and Brisbane city.